1986
DOI: 10.1002/eji.1830160611
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of human mature thymocytes: Existence of a T3+48 intermediate stage

Abstract: A T3 complex-bearing subpopulation was characterized within an in vivo cycling T4-8- early thymocyte compartment which contains cells constitutively expressing interleukin 2 and transferrin receptors. We show differentiation in vitro of both mature subsets of thymocytes (T3+4+8- and T3+4-8+) from the above T4-8- compartment, their appearance being preceded by cells in a T3+4-8- intermediate stage. Furthermore, those mature thymocytes generated in vitro contain functionally competent cells which use T3, T4 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Indeed, a mutation in the extracellular domain of CD95L has been reported in a patient diagnosed as having atypical lupus erythematosus. 23 In humans, TCR-␣␤ DN T cells are normally found in the thymus, 24 skin, 25 and peripheral blood. 25,26 They represent a small subpopulation of peripheral blood lymphocytes in most healthy adults but are increased in some patients with systemic and cutaneous autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a mutation in the extracellular domain of CD95L has been reported in a patient diagnosed as having atypical lupus erythematosus. 23 In humans, TCR-␣␤ DN T cells are normally found in the thymus, 24 skin, 25 and peripheral blood. 25,26 They represent a small subpopulation of peripheral blood lymphocytes in most healthy adults but are increased in some patients with systemic and cutaneous autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Most CD1 + double-positive thymocytes generated in vitro bear cytoplasmic TCR/3 chain, indicating that they are a/3 pre-T cells, and some may express low levels of TCR -CD3 on the cell membrane. CD1 + TCR-CD3+ thymocytes cannot be expanded in vitro, nor can normal peripheral mature CD1 + T cells be detected ex vivo (Table 1; unpublished observations). Interestingly enough, a minor subset (<5%) of CD1-3 + double-positives occurs in vivo We have previously shown that polyclonal activators such as PHA and IL2 stimulate the generation of such CD1-3+ double-positives from CD1-double-negatives in vitro (32). CD1 -3+4+8+ thymocytes are functionally competent and can proliferate in the presence of IL2 (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…CD1 + TCR-CD3+ thymocytes cannot be expanded in vitro, nor can normal peripheral mature CD1 + T cells be detected ex vivo (Table 1; unpublished observations). Interestingly enough, a minor subset (<5%) of CD1-3 + double-positives occurs in vivo We have previously shown that polyclonal activators such as PHA and IL2 stimulate the generation of such CD1-3+ double-positives from CD1-double-negatives in vitro (32). CD1 -3+4+8+ thymocytes are functionally competent and can proliferate in the presence of IL2 (32,33). We therefore conclude that CD1 + and CD1 -, CD4-8-cells can act as precursors for two distinct subsets of doublepositive thymocytes in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data underline a critical point in T cell development, namely the growth "signals" involved in the intrathymic differentiation process. In this regard, the expression of receptors for the IL-2 growth molecule in early double-negative thymocytes, shown to contain the precursors of mature T cells (1), has been reported in mouse (47,52) and humans (41), and the potential role of the IL-2 pathway in T cell development has been suggested in both systems (34,(53)(54)(55)(56) .…”
Section: Discussionmentioning
confidence: 99%